2023
DOI: 10.1186/s12870-023-04325-5
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin strongly enhances the Agrobacterium- mediated transformation of carnation in nitrogen-depleted media

Abstract: With the rising demand for new cultivars of carnation, efficient transformation protocols are needed to enable the bioengineering of new traits. Here, we established a novel and efficient Agrobacterium-mediated transformation system using callus as the target explant for four commercial carnation cultivars. Leaf-derived calli of all cultivars were inoculated with Agrobacterium tumefaciens strain LBA4404 containing the plasmid pCAMBIA 2301 harboring genes for β-glucuronidase (uidA) and neomycin phosphotransfera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Nowadays, floriculture is a dynamic, global and fast-growing industry [24], and at the wholesale market, carnation (Dianthus caryophyllus L.) is one of the most popular cut flowers, with a rich flower color and form, ranking next only to rose [25]. A large breeding research implemented to date, as indicated by the increased number of carnation cultivars worldwide, has demonstrated the carnation's appealing and unique qualities, including different flower colors, sizes and shapes; enhanced fragrance; resistance to susceptibility; increased yield; and extended vase life [26]. The increased needs for carnation production mirrored the high research interest for the evaluation of different growing media for carnation production [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, floriculture is a dynamic, global and fast-growing industry [24], and at the wholesale market, carnation (Dianthus caryophyllus L.) is one of the most popular cut flowers, with a rich flower color and form, ranking next only to rose [25]. A large breeding research implemented to date, as indicated by the increased number of carnation cultivars worldwide, has demonstrated the carnation's appealing and unique qualities, including different flower colors, sizes and shapes; enhanced fragrance; resistance to susceptibility; increased yield; and extended vase life [26]. The increased needs for carnation production mirrored the high research interest for the evaluation of different growing media for carnation production [27][28][29].…”
Section: Introductionmentioning
confidence: 99%